Проблемні аспекти та перспективи інноваційного розвитку сільськогосподарського машинобудування - Сисоліна, Н. П.; Савеленко, Г. В.; Сисоліна, І. П.; Sysolina, N.; Savelenko, Н.; Sysolina, І. (ЦНТУ, 2018)
В статті досліджено сучасні умови функціонування підприємств сільськогосподарського машинобудування, виявлено проблеми, з якими вони стикаються та які уповільнюють їх розвиток, окреслено можливі перспективні засади управління та запропоновано нові підходи щодо підвищення конкурентоспроможності таких підприємств. Обґрунтовано необхідність державної підтримки вітчизняних підприємств сільськогосподарського машинобудування на мезо- та макрорівнях. На основі дослідження комплексу показників побудовано модель механізму інноваційного розвитку. At the present stage, domestic agricultural machine building does not correspond to innovative development. The purpose of the article is to study the main tendencies and substantiation of approaches to increase competitiveness of agricultural machinery enterprises. In the article the modern conditions of functioning of agricultural machinery enterprises are investigated and the problems, with which they encounter, which slow down their development, are revealed. It also outlines possible perspective management principles and proposes new approaches to improving the competitiveness of agricultural machinery enterprises. It was established that the state does not pay enough attention to the issue of updating the technological equipment of agricultural machinery enterprises, introducing the achievements of scientific and technological progress in the production of domestic agricultural machinery. The necessity of developing a new state program of support of domestic enterprises of agricultural machine-building at the meso- and macro levels was substantiated. The necessity of reorientation of agricultural machine-building enterprises for the production of modern high-tech equipment, which corresponds to world standards and can compete with foreign analogues, is indicated as it is the main way to enter international markets of agricultural machinery and preservation of the national consumer. On the basis of research of a complex of indicators, the model of the mechanism of innovation development is constructed.
Problematic Aspects and Perspectives of Innovative Development of Agricultural Machine Building
Keywords: сільськогосподарське машинобудування; конкурентоспроможність підприємств; інноваційний розвиток; управління підприємством; agricultural machine building; enterprise competitiveness; innovation development; management